PENGARUH PEMASARAN SOSIAL MEDIA TERHADAP KEPUTUSAN PEMBELIAN DOMINIQUE’S DENGAN MINAT BELI SEBAGAI VARIABEL MEDIASI - Tio Phillbert (Jurnal Performa)
The purpose of this study is to examine the impact of social media marketing on consumer purchasing decisions as mediated by Dominique's consumer purchasing interest. Respondents are Dominique's customers who have purchased products and visited 52 people who were chosen using a non-probability with purposive sampling technique. The data for this study were gathered by distributing questionnaires via Google forms and analyzed with PLS-SEM. The findings of this study demonstrate that marketing media have a significant influence on buying interest and consumer purchasing decisions. Furthermore, through purchase intention, social media marketing indirectly influences purchasing decisions